2011
DOI: 10.1523/jneurosci.4790-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Specific Adaptation: Can It Be a Neural Correlate of Behavioral Habituation?

Abstract: Habituation is the most basic form of learning, yet many gaps remain in our understanding of its underlying neural mechanisms. We demonstrate that in the owl's optic tectum (OT), a single, low-level, relatively short auditory stimulus is sufficient to induce a significant reduction in the neural response to a stimulus presented up to 60 s later. This type of neural adaptation was absent in neurons from the central nucleus of the inferior colliculus and from the auditory thalamus; however, it was apparent in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 71 publications
2
81
0
Order By: Relevance
“…This phenomenon is relatively long-lasting (up to 60 s) and operates both on artificial and natural stimuli (Netser et al, 2011). Its relationship with the type of sensitivity found in the present study remains as yet unclear because of differing stimulation paradigms; it may be that they represent two different mechanisms, but it may also be that secondary auditory forebrain circuits compute novelty of sound objects in natural auditory scenes and modulate tectal responses (Netser et al, 2011).…”
Section: Discussionmentioning
confidence: 59%
“…This phenomenon is relatively long-lasting (up to 60 s) and operates both on artificial and natural stimuli (Netser et al, 2011). Its relationship with the type of sensitivity found in the present study remains as yet unclear because of differing stimulation paradigms; it may be that they represent two different mechanisms, but it may also be that secondary auditory forebrain circuits compute novelty of sound objects in natural auditory scenes and modulate tectal responses (Netser et al, 2011).…”
Section: Discussionmentioning
confidence: 59%
“…This was done in the OT of barn owls by presenting sequences of identical sounds and measuring unit responses as a function of the position of the stimulus in the sequence. Remarkably, it was found that the memory trace of the SSA in the OT can be up to 60 s long (Netser et al 2011). A single, short (300 ms), and low intensity (20 dB above threshold) stimulus was sufficient to induce a reduction in the neural response to the same stimulus occurring 60 s later.…”
Section: The Memory Trace Of Adaptationmentioning
confidence: 98%
“…Recently, auditory adaptation was characterized systematically in the barn owl's OT (Reches and Gutfreund 2008;Netser et al 2011). Oddball and repeated sequence protocols (see Fig.…”
Section: Stimulus-specific Adaptation In the Otmentioning
confidence: 99%
See 2 more Smart Citations